2011
DOI: 10.1097/jsm.0b013e31822cf105
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of ST Elevation on Athletic Screening

Abstract: Early repolarization is not associated with cardiac death and has patterns that help distinguish it from STE associated with cardiac conditions, such as myocardial ischemia or injury, pericarditis, and the Brugada syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Early repolarisation is a common finding in trained athletes and considered a benign ECG pattern in apparently healthy, asymptomatic individuals 24 25. Depending on how it is defined, early repolarisation is reported in up to 35–91% of trained athletes and is more prevalent in young males and black/Africans 12 13 25 26.…”
Section: Normal Ecg Findings In Athletesmentioning
confidence: 99%
See 1 more Smart Citation
“…Early repolarisation is a common finding in trained athletes and considered a benign ECG pattern in apparently healthy, asymptomatic individuals 24 25. Depending on how it is defined, early repolarisation is reported in up to 35–91% of trained athletes and is more prevalent in young males and black/Africans 12 13 25 26.…”
Section: Normal Ecg Findings In Athletesmentioning
confidence: 99%
“…Depending on how it is defined, early repolarisation is reported in up to 35–91% of trained athletes and is more prevalent in young males and black/Africans 12 13 25 26. Early repolarisation is most common in the precordial leads but can be present in any lead 27–29.…”
Section: Normal Ecg Findings In Athletesmentioning
confidence: 99%
“…Of the 51 papers included in analysis, 32 papers discussed Black athletes. Of the included papers, 26 found that there was a significant difference between Black athlete and Caucasian athlete ECGs [ 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], but six papers concluded there were no significant differences between athletes [ 38 , 39 , 40 , 41 , 42 , 43 ]. Of the 26 papers that reported differences, 19 identified specific differences between groups of athletes, while the other seven papers noted an overall rate of abnormal ECGs noted by various criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Lateral T-wave inversion, leads V5, V6, and I, and aVL were found as more common in five papers, ranging from 0.9% to 6.1% in Black athletes and from 0% to 0.3% in Caucasian athletes [ 15 , 16 , 27 , 28 , 36 ]. ST elevation differences were identified in eight papers, commonly found in the anterior and lateral leads, ranging from 11% to 85% in Black athletes and from 1% to 61% in Caucasian athletes [ 15 , 16 , 17 , 23 , 28 , 30 , 32 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…229,[232][233][234] The potential significance of this alteration in ECGs to population-based preparticipation screening is unresolved at present.…”
Section: Reliability Of Ecg Diagnostic Criteriamentioning
confidence: 99%